Effects of acetazolamide on linear growth in children with pseudotumor cerebri syndrome - Sheldon, Claire A.; Reggie, Sara N.; Paley, Grace L.; McCormack, Shana E.; Liu, Grant T. (Frontiers in Ophthalmology, 2023)
Background/Introduction: While oral acetazolamide is a cornerstone of management of adult and pediatric PTCS, previous studies have suggested that acetazolamide used in children with other conditions may influence growth. Aims and Methods: Retrospective chart review involving a single tertiary medical center. Thirty-four children with definite or probable PTCS were identified. Analysis was restricted to individuals from whom anthropometric data were available before and during acetazolamide treatment (n=22). Results: Half of individuals (n=11/22) showed a decline in BMI Z-scores. Sixty-three percent (n=14/22) showed a decrease in height Z-scores during treatment with acetazolamide; in 6 of these 14 children who had complete data, 3 showed at least a partial recovery of height Z-scores after discontinuation of acetazolamide. Conclusion: Acetazolamide may be associated with growth suppression in some children treated for pediatric PTCS. In some cases, the growth suppression appears to reverse once the acetazolamide is stopped.